A post-detection maximum ratio combiner. Experimental assessment on high diversity underwater channels - Silva, A. (2014)
Maximum Ratio Combiner (MRC) is a diversity combining technique applicable to underwater communications when the data transmitted by a single projector is received by more than one antenna/node. Post Detection MRC (PD-MRC) performs a weightedsum over initial detected outputs of multiple nodes. PDMRC can be applied to noise-only or ISI-only channels with the weights computed from the signal to noise ratio or from the channel impulse response of each node, respectively. In this paper it is shown that in the presence of noisy-ISI channels the weighs can be computed from the detector output constellation of each node. A performance of the PD-MRC is evaluated using real data collected during RADAR’07 experiment. Results show that a gain is always attained using two nodes in the PDMRC as compared to the node having the best MSE. Moreover, the PD-MRC gain is higher when both nodes present a similar MSE.